2019
DOI: 10.1371/journal.pone.0223951
|View full text |Cite
|
Sign up to set email alerts
|

A randomized crossover trial comparing the Nifty cup to a medicine cup in preterm infants who have difficulty breastfeeding at Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ghana

Abstract: IntroductionPreterm infants make up the majority of the 9 million babies born in Africa and South Asia requiring supplemental feedings as they transition to exclusive breastfeeding. The World Health Organization recommends the use of a cup to feed newborns with breastfeeding difficulties in low-resource settings. We set out to evaluate the Nifty cup, a new feeding cup designed specifically for infants with breastfeeding difficulties.Materials and methodsWe conducted a randomized clinical trial in Ghana. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
11
Order By: Relevance
“…9 However, in previous studies, duration of feed and spillage were only measured qualitatively by asking mothers/caregivers. 10,11 It has also been suggested by previous research that if a neonate spends more than 20 min feeding, the energy expenditure increases, which can result in a decrease in weight gain. 12 In the present study, it was observed that the length of hospitalization was 13.0 ± 11.8 (1−77) days, and the PMA at discharge was 34 weeks.…”
Section: Discussionmentioning
confidence: 94%
“…9 However, in previous studies, duration of feed and spillage were only measured qualitatively by asking mothers/caregivers. 10,11 It has also been suggested by previous research that if a neonate spends more than 20 min feeding, the energy expenditure increases, which can result in a decrease in weight gain. 12 In the present study, it was observed that the length of hospitalization was 13.0 ± 11.8 (1−77) days, and the PMA at discharge was 34 weeks.…”
Section: Discussionmentioning
confidence: 94%
“…9 However, in previous studies, duration of feed and spillage were only measured qualitatively by asking mothers/caregivers. 10, 11 It has also been suggested by previous research that if a neonate spends more than 20 min feeding, the energy expenditure increases, which can result in a decrease in weight gain. 12…”
Section: Discussionmentioning
confidence: 94%
“…Higienizado através de fervura em água por 10 minutos, autoclave ou desinfecção química. 13 Fonte: Autores Figura 4-Copo Dosador Padrão: Capacidade de 30 ml de volume, translúcido, marcado com escala de graduação, confeccionado em plástico comum, tipicamente usado para administrar medicamentos. 13 Fonte: Autores Figura 5-Copo Descartável: copo plástico de 50ml, não reutilizável, frequentemente indicado para consumo de café.…”
Section: Revista Observatorio Deunclassified
“…O aleitamento através do copo promove mais estímulos sensoriais e neuromotores ao lactente, bem como melhor capacidade de controle da ingestão de leite. 13 Pode ser utilizado por bebês prematuros, mesmo quando ainda não coordenam adequadamente as funções requeridas para mamar, já que a deglutição desenvolve-se precocemente na vida fetal em relação à coordenação com a sucção e a respiração. 14,15 Estudos com eletromiografia oral mostram que o copo, diferente dos dispositivos com bico artificial, aciona a musculatura mastigatória de forma semelhante à ordenha do peito, com maior movimentação da mandíbula e da língua.…”
Section: Introductionunclassified
See 1 more Smart Citation